INFLUENCE OF PRODUCT QUALITY AND PRICE ON PURCHASE DECISIONS THROUGH WORD OF MOUTH AS INTERVENING VARIABLES - Della Asmaria Putri; Azizah Hidmi Shafitri (Manajemen Bisnis, 2021)
ABSTRACT This study aims to determine how much influence product quality and price have on purchasing decisions through word of mouth as an intervening variable (a case study on the kitchen culinary of mbok ghenduk purus in the city of Padang). This study uses a population of visitors with 98 samples obtained through purposive sampling method. This study uses multiple linear regression analysis. The results of this study indicate that there is a positive and significant effect on product quality on word of mouth, price has a positive and significant effect on word of mouth, product quality has a positive and significant effect on purchasing decisions, prices have a positive and significant effect on purchase decisions, word of mouth has an effect positive and significant impact on purchasing decisions, the indirect effect of product quality on purchasing decisions through word of mouth is greater than the direct effect of product quality on purchasing decisions, so it can be concluded that word of mouth is able to become an intervening variable between product quality and purchasing decisions. Direct price on purchasing decisions through word of mouth is greater than the direct effect of price on purchasing decisions, so it can be concluded that word of mouth can be an intervening variable between price and purchase decisions. Finally, the authors suggest that purchasing decisions can affect product quality and price intervening with word of mouth.